Metastatic calcinosis cutis in a dialysis patient - Bapoo, Nabeel; Chothia, Mogamat-Yazied; Stead, Piers A; Ally, Ismail (African Journal of Nephrology, 2023)
Metastatic calcinosis cutis is an uncommon complication of end-stage kidney disease but has severe and disabling effects. Its development is attributed to disorders of calcium and phosphate metabolism associated with secondary hyperparathyroidism. The mainstay of treatment remains medical therapy; however, in refractory cases a parathyroidectomy is indicated. We describe the case of a 22-year-old female with refractory hyperparathyroidism treated with a subtotal parathyroidectomy resulting in complete resolution of metastatic calcinosis cutis of the hands. Clinicians should be aware that this complication can occur soon after the initiation of dialysis and that rapid complete resolution can be achieved with parathyroidectomy.